DATA PREPARATION FOR AN ACCURATE ENHANCED OIL RECOVERY LABORATORY TEST BY USING SURFACTANT FLOODING METHOD - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2005)
In preparation of the study, x core plugs are drilled. Determination of basic parameter and identification of core plug sample are carried out following the API-RP 40. For example, the tests of physical properties, i.e. grain density (gr/cc), weight, grain volume (cc), pore volume (cc), posority (%), and air permeability (Ka.mD).